Pulmonary Tuberculosis Coinfected with COVID-19 Compounded by Bacterial Superinfection: A Case Report and Critical Appraisal of The Evidence Regarding Its Mortality - Kemal Akbar Suryoadji; Baiq Amalia Utami; Fairuzia Fiyanti Putri; Hilma Nur Faiza; Kezia Alicia Theresia Manik; Fathiyah Isbaniyah; Jamal Zaini (Jurnal Respirologi Indonesia, 2023)
Background: The WHO has declared COVID-19 as a global pandemic. However, Indonesia is also challenged by high burden of tuberculosis (TB). In this study, reported an active pulmonary TB case coinciding with COVID-19 but deceased due to bacterial infection. There is a need to further explore this new problem in developing countries to determine the prognosis of COVID-19 patients with tuberculosis infection.Methods: A comprehensive literature search was conducted by using databases such as The Cochrane Library, PubMed, Google Scholar, EBSCO-Host, and Scopus, including systematic reviews of cohort studies, cohorts, and case controls. As many as 309 studies were identified, after screening for duplicates and against the inclusion and exclusion criteria, three studies were included for critical appraisal.Results: The meta-analysis by Gao et al included two studies with an odds ratio (OR) of 1.4 [95% CI=0.1-18.93], the cohort study by Sy et al reported a relative risk (RR) of 2.17 [95% CI=1.4-3.37], and Motta et al showed that COVID-19 patients with tuberculosis had a mortality rate of 11.8% [95% CI=7.75-15.45]. Conclusion: TB has yet to be an identified as a major predictor of increased mortality in COVID-19 patients but can be considered a predictor of increased severity in COVID-19 patients. Studies with a bigger sample size and better study design are suggested to obtain new evidence.